THE INFLUENCE OF WORK COMPETENCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN ACEH ENERGY AND MINERAL RESOURCES DEPARTMENT - T. Andi Roza; Syarifah Mauli Masyithah; Zuliani Zuliani; Arisnaini Arisnaini; Rahmi Rahmi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to analyze the influence of competence and work discipline on employee performance at the Aceh Energy and Mineral Resources Office. The sample size of this study was 58 employees. The results of the research on the partial test of competency variables affect employee performance at the Aceh Energy and Mineral Resources Office. Work Discipline affects the performance of employees at the Aceh Energy and Mineral Resources Office. Then the Simultaneous Test between competency and work discipline variables influences employee performance at the Aceh Energy and Mineral Resources Office. Partially, competence affects employee performance at the Aceh Energy and Mineral Resources Service with a value of tcount (2.395) greater than ttable (2.004). Partially, work discipline affects employee performance at the Aceh Energy and Mineral Resources Office with a value of tcount (3.557) more than the value of ttable (2.004). Simultaneously competence and work discipline affect employee performance at the Aceh Energy and Mineral Resources Office with a Fcount (13.578) greater than Ftable (3.168).